2023
DOI: 10.1039/d3bm00212h
|View full text |Cite
|
Sign up to set email alerts
|

Does non-thermal plasma modify biopolymers in solution? A chemical and mechanistic study for alginate

Abstract: In the last decades, non-thermal plasma has been extensively investigated as a relevant tool for various biomedical applications, ranging from tissue decontamination to regeneration and from skin treatment to tumor...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
(118 reference statements)
0
5
0
Order By: Relevance
“…A recent publication provides a mechanistic insight supported by computational and experimental data on how plasma may be interacting with alginate to introduce different chemical modifications. [ 22 ] In their study, the authors report the possible formation of different organic peroxides and intermediate products as the result of plasma oxidation of alginate. Nevertheless, it is a different research question to which extent these chemical modifications have a biological effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent publication provides a mechanistic insight supported by computational and experimental data on how plasma may be interacting with alginate to introduce different chemical modifications. [ 22 ] In their study, the authors report the possible formation of different organic peroxides and intermediate products as the result of plasma oxidation of alginate. Nevertheless, it is a different research question to which extent these chemical modifications have a biological effect.…”
Section: Discussionmentioning
confidence: 99%
“…Related to this, 1‐min treatment time may also be too short for biologically relevant oxidations to occur or accumulate in alginate. [ 22 ] It would be interesting to explore in the future if higher plasma treatment times lead to alginate PTHs with more pronounced (and non‐H 2 O 2 ‐mediated) biological effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25,26] Experiments performed in polysaccharides (alginate, methylcellulose) and proteins (albumin, gelatin, lysozyme, RNase, and superoxide dismutase) solutions showed that direct plasma treatment is able to fragment and to oxidize, to a different extent, the biopolymers, affecting their functionality, and generating intermediates with different reactivity. [14,[27][28][29][30] Finally, a direct plasma treatment of biopolymer solutions leads to the enhancement of long-lived species (H 2 O 2 and NO 2 − ) in solution, likely proceeding through the generation of organic peroxides and/or by involving transient RONS like O and HO radicals. [29,31] Ultimately, organic-containing solutions may expectedly contain the most diverse range of biologically relevant species: organic biologically relevant molecules and the whole range of inorganic RONS as described for the two previous types of aqueous systems.…”
mentioning
confidence: 99%
“…[14,[27][28][29][30] Finally, a direct plasma treatment of biopolymer solutions leads to the enhancement of long-lived species (H 2 O 2 and NO 2 − ) in solution, likely proceeding through the generation of organic peroxides and/or by involving transient RONS like O and HO radicals. [29,31] Ultimately, organic-containing solutions may expectedly contain the most diverse range of biologically relevant species: organic biologically relevant molecules and the whole range of inorganic RONS as described for the two previous types of aqueous systems.…”
mentioning
confidence: 99%